Nurses’ expectations towards postgraduate education - Majchrowska, Anita; Bogusz, Renata (Nursing in the 21st Century, 2012)
NURSES’ EXPECTATIONS TOWARDS POSTGRADUATE EDUCATIONIntroduction. Progressing professionalization of nursing requires constant education to expand and update one’s professional knowledge. This statutory duty can be met thanks to the constantly broadened range of forms of education and professional training, the latter being specialization, qualification, in-service and specialist trainings. Furthermore, nurses turned out to be particularly interested in undertaking training, so the nature of their expectations towards postgraduate education is worth investigating.Aim. The aim of this research is to identify nurses’ expectations towards postgraduate education.Material and method. An auditorium questionnaire survey was conducted in 2012 among 102 nurses who participated in professional training delivered by the Centre of Postgraduate Education, Medical University of Lublin.Results. The main benefits for those who undertake postgraduate training refer to opportunity to expand one’s specialist knowledge as well as one’s own satisfaction with higher qualifications. The surveyed noted that sense of self- and job security is also a significant factor, though they were ambiguous when identifying benefits for the whole professional group of nurses. The respondents mentioned increased professional self-reliance, better quality of nursing, as well as growing professionalization of nursing and raised job prestige among the society. They expect that becoming a specialist will result in a pay rise and greater professional independence, the latter meaning more active participation in the decision-making process.Conclusions: Nurses who undertake postgraduate education expect, above all, extension of professional knowledge and consequently increase of professional independence. It is worth noting that nurses expect higher qualifications to influence their salary.